Editorial: gene–environment interplay in child psychology and psychiatry – challenges and ways forward. (5th September 2013) - Petrill, Stephen A.; Bartlett, Christopher W.; Blair, Clancy
Abstract : This special issue in the Journal of Child Psychology and Psychiatry presents several invited articles examining gene–environment interplay in child development and psychopathology. Models of gene–environment interplay have been exhaustively discussed in the literature, including an important contribution by Rutter, Moffitt and Caspi (2006) published in this journal.